A influ??ncia da estrat??gia de terceiriza????o de sistemas de informa????o no alinhamento entre estrat??gia de neg??cios de T.I. - Gon??alves, Andr??a de Paiva (2006)
The Information Technology (IT) has an important function in the communication and in competencies generation in the organizations, however, the simple use of the IT is not a competitive differential anymore, the differential is the way as the organizations use it. It is necessary to use it by strategic ways to generate value to the business. Another subject that is much discussed in academic researches, and each time more used by the companies, is the outsourcing of IT resources, more specifically, information systems outsourcing. As main objective, this study proposes to verify the influence that the outsourcing strategy of information systems has on the alignment between the business strategy and IT strategy. The research method used is the case study, being the data collection carried through the analysis of documents and interviews with directors of business and IT areas, based in the models of alignment between business and IT strategy and the theories related with the information systems outsourcing identified in literature. The Alfa Financial Conglomerate was chosen for the accomplishment of the field research, for filling the criteria of selection of organizations for this research, therefore it presents solid experience in IT outsourcing processes. The outsourcing experience is common to the entire financial conglomerate, due to the fact that the IT administration is common to all companies of the group. It is verified for the presented data, adherence to the models of Luftman (2000) and Reich and Benbasat (2000) and is concluded that the Alfa Financial Conglomerate presents high level of strategic alignment between business and IT, not being in its totality an optimized process, however, walking for such classification. Moreover, the influence that the outsourcing strategy of information systems exerts on the alignment is more strongly identified in the application of the model of Luftman (2000). As conclusion have been proposed bases for a model of alignment between business and IT strategy that complain the junction of the variants identified by Luftman (2000) and Reich and Benbasat (2000) for such use, giving emphasis to the ones that makes possible to identify the influence of the information systems outsourcing in the alignment. As theoretical contribution, it is believed that the realized research has allowed not only the test of the models, but also qualitative advances that can support new proposals and research of bigger amplitude and refinement with the inclusion of a new variable: the information systems outsourcing. In terms of practical contributions, is expected that this research has collaborated validating and stimulating the use of a tool for the taking of decisions regarding the information systems outsourcing, in such way that this decision does not harm and, been preferentially used in benefit of the alignment between the business and IT strategy.